2015
DOI: 10.1002/jobm.201500080
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of ITS region of rRNA in Microcystis (Cyanobacteria) populations in Erhai Lake (China) and their correlation with eutrophication level

Abstract: Previous studies on spatiotemporal changes of Microcystis genotypes have shown that the existence and succession of dominant genotypes always occur in eutrophicated freshwater bodies. However, few studies have focused on the correlation between genotype composition and eutrophication level. In the present study, clone libraries of the internal transcribed spacer (ITS) of rrn operon were sequenced from Microcystis populations in Erhai Lake, a subtropical plateau lake in the preliminary eutrophication stage. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…The Microcystis ITS region for Genotype I was identical to that for Microcystis spp. reported from Erhai Lake in China (GenBank accession numbers: KF207342.1 and KF207087.1), Joumine Reservoir in Tunisia (HQ389359.1 and HQ389360.1), and Loire River in France (FJ474921.1) [ 60 62 ]. Microcystis Genotype VI had an identical ITS sequence to Microcystis spp.…”
Section: Resultsmentioning
confidence: 99%
“…The Microcystis ITS region for Genotype I was identical to that for Microcystis spp. reported from Erhai Lake in China (GenBank accession numbers: KF207342.1 and KF207087.1), Joumine Reservoir in Tunisia (HQ389359.1 and HQ389360.1), and Loire River in France (FJ474921.1) [ 60 62 ]. Microcystis Genotype VI had an identical ITS sequence to Microcystis spp.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to Lushui Reservoir, a larger cyanobacterial diversity was observed in Erhai Lake. In a previous investigation, an extremely large number of genotypes were detected for Microcystis in Erhai Lake [ 9 ]. A negative correlation was determined between the Microcystis diversity and eutrophication levels [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, each of above genera contains both toxin-producing and nontoxin-producing species. Microcystis is the most frequently reported bloom-forming cyanobacterium, which often occurs as dense blooms in summer and autumn [ 9 , 10 , 11 ]. In subtropical and temperate lakes, Dolichospermum and Aphanizomenon usually become dominant when the abundance of Microcystis decreases in winter and spring [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that the Microcystis abundance has a negative correlation with bacterial (e.g., Actinobacteria) diversity. In Erhai Lake, Song et al identified 473 Microcystis genotypes by seasonal monitoring using internal transcribed spacer (ITS) genes and amplification primers [57]. The data indicated that the early stage of eutrophication in Erhai Lake might result in high diversity of Microcystis due to the negative relationship between the diversity of ITS genotypes and TN/TP.…”
Section: Edna Methods For Eutrophication and Hab Controlmentioning
confidence: 99%